Novel Adaptation of Ancika: Dia yang Bersamaku 1995 Into Film and Its Implications for Indonesian Language Learning in Senior High School - Dimas Dwi Pramudia; Muhammad Fuad; Aditya Pratama; Munaris Munaris (LinguaScopes: International Journal of Language Education, 2026)
This study aims to describe the adaptation process of the novel Ancika: Dia yang Bersamaku 1995 into its film version and to explain its implications for Indonesian language learning in Senior High School (SMA). The adaptation of a novel into a film is a process that not only transfers the story but also involves structural and narrative transformations due to differences in the characteristics of each medium. This research employs a descriptive qualitative method. The data sources consist of the novel Ancika: Dia yang Bersamaku 1995 and its film adaptation. The data were analyzed by comparing the intrinsic elements of the novel and the film namely plot, characters, and setting based on adaptation theory, which includes reduction, addition, and variation changes. The results show that reduction is carried out by omitting certain narrative details to achieve dramatic effectiveness; additions are made to strengthen conflicts and clarify relationships between characters; and variation changes occur through modifications in the presentation of events without eliminating the core of the story. The findings of this study have implications for Indonesian language learning in Senior High School, particularly in drama text material for Phase F Grade XI of the Merdeka Curriculum, as contextual teaching material that supports the development of students’ critical, analytical, and creative thinking skills.